Evaluation of the Quality Characteristics of Composite Flour Bread Produced from Wheat-Root Tuber and Wheat-Grain Legume Flour Blends - Agbara, G. I.; Ige, A. C.; Agbara, N. H.; Ahmad, G.; Masaya, F. A.; Aliyu, B. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
Adoption of composite flours for baked and non-baked goods has been trending and the underlying reasons include economic consideration, nutritional enhancement and amelioration of noncommunicable diseases through consumption of functional foods. Comparative study of the performance of popular food crop flours in bread making is not well documented although a lot work abound in the literature concerning specific blends from wheat and crop flours studied separately. But in the present study, comparative effects of 30% substitution of wheat flour with two common root tuber flours: sweet potato (Ps) and cassava (Ca) and three common grain legume flours in Nigeria: soybean (S), cowpea (Co), bambara groundnut (B) on bread quality were studied. Soybean, cowpea, and bambara groundnut were soaked and decorticated, toasted mildly and milled to obtain flours. Cassava and sweet potato roots were peeled, chopped, oven dried, milled and sieved. All purpose wheat flour was used to form blends with non-wheat flours on a constant ratio of 70:30 replacement weight basis, a total of five flour blends were obtained while 100% wheat flour served as the control. Bread were prepared using straight dough method of AACC. Thereafter, standard procedures were used to evaluate the proximate composition of the blends and bread, as well as the bread physical and sensory properties. Data generated were subjected to analysis of variance and mean values ±SE were reported. Consistently, soybean and bambara groundnut flours had significant higher content of protein, ash, crude fat and crude fibre than cassava and sweet potato flours which contained higher level of carbohydrates. The moisture contents of the flours were low and comparable. The moisture, crude protein, crude fat, total ash, crude fibre and carbohydrate contents of the flour blends and the refined wheat flour varied significantly (p<0.05) from 8.08-10.27%, 7.52-13.93%, 2.08-4.06%, 0.81-1.85%, 2.11-4.51% and 67.75-76.66% respectively. The same trend was repeated in the proximate composition of the composite flour breads although the calorific values decreased due to decrease in carbohydrate contents (58.00-47.64%), protein (6.37-11.98%), and increase in moisture (26.71-29.75%), relative to the values observed in the flour blends. Bread weights (196-223g) were comparable but the bread volumes (429-988ml) and specific loaf volumes (2.24-4.82ml/g) varied significantly (p<0.05) and wheat bread had the highest and legume flour treated breads had the least. Organoleptic properties of the wheat bread were rated better in some attributes however not significantly (p<0.05) different from those of 30% sweet potato and cassava breads. It was concluded that although nutritional value of legume containing breads were greater yet their bread volumes were depressed more, the higher protein of grain legume flours not withstanding confirming the fact that quality not quantity of the protein is the determinant factor in bread making potential of flours.